2012
DOI: 10.1142/s0217732312501829
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic of the Ghost Dark Energy Universe

Abstract: Recently, the vacuum energy of the QCD ghost in a time-dependent background is proposed as a kind of dark energy candidate to explain the acceleration of the Universe. In this model, the energy density of the dark energy is proportional to the Hubble parameter H, which is the Hawking temperature on the Hubble horizon of the Friedmann-Robertson-Walker (FRW) Universe. In this paper, we generalized this model and choice the Hawking temperature on the so-called trapping horizon, which will coincides with the Hubbl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 50 publications
10
39
0
Order By: Relevance
“…Now, since there are some works showing that a dark energy candidate may modify the horizon entropy [19][20][21][22][23], can one make a relation between the energy density of dark energy candidate and the general entropy relation? Here, we are going to investigate the possibility of establishing a relation between these attempts and the generalized entropy proposed by Tsallis et al [54], which is also supported by the quantum cosmology considerations [55].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, since there are some works showing that a dark energy candidate may modify the horizon entropy [19][20][21][22][23], can one make a relation between the energy density of dark energy candidate and the general entropy relation? Here, we are going to investigate the possibility of establishing a relation between these attempts and the generalized entropy proposed by Tsallis et al [54], which is also supported by the quantum cosmology considerations [55].…”
Section: Introductionmentioning
confidence: 99%
“…It was also argued that a dark energy candidate, due to its unknown nature, may modify the apparent horizon entropy in various theories of gravity [19][20][21][22][23]. In fact, by decomposing ρ to ρ D +ρ o , in which ρ D denotes the energy density of dark energy candidate and ρ o includes the energy density of other parts of cosmos, using the Friedman equation (10), continuity equation (4) together with the unified first law of thermodynamics and the Clausius relation, one can obtain a new relation for the horizon entropy as…”
mentioning
confidence: 99%
“…But, since the origin of DE is unknown, it may have either a geometrical or physical origin, one can expect that the DE candidate may affect the horizon entropy. By the same token, it is shown that the ghost dark energy and its generalization, as the dynamics candidates for DE, may also add an additional term to the entropy of various horizons leading to modify the Bekenstein limit [76,77]. Therefore, it seems that the dynamics model of DE may lead to modify the horizon entropy and thus, the Bekenstein limit.…”
Section: Introductionmentioning
confidence: 99%
“…GDE has attained significant attention and various aspects have been discussed such as interacting GDE models (Sheykhi and Movahed 2012), thermodynamics (Feng et al 2012), correspondence with scalar field models (Karami and Fahimi 2013), f (R) gravity (Jawad 2014; Saaidi et al 2012), f (T ) gravity (Karami et al 2013a) and Brans-Dicke theory (Ebrahimi and Sheykhi 2011). In (Cai et al 2012), authors presented a generalized GDE of the form αH + βH 2 and discussed its dynamical evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of Einstein-Hilbert action is another approach to un-ravel the mysterious nature of DE and various candidates have been proposed namely, f (R) gravity (Capozziello and Faraoni 2011), f (T ) (Ferraro and Fiorini 2007;, where T is the torsion scalar, GaussBonnet gravity (De Felice and Tsujikawa 2010), f (R, T ) gravity (Alvarenga et al 2013a;Harko et al 2011;Zubair 2012, Shabani andFarhoudi 2013;Noureen andZubair 2015, Noureen et al 2015), where T is the trace of the energy-momentum tensor and f (R, T, R µν T µν ) gravity (Nojiri and Odintsov 2010;2011a;Haghani et al 2013;Zubair 2013a, 2013b). Cosmological reconstruction in modified theories is one of the significant aspects in cosmology.…”
Section: Introductionmentioning
confidence: 99%